Batocera rufomaculata (Coleoptera: Cerambycidae), a New Insect Record on Casuarina equisetifolia L. in India - Singh, Ranjeet; Sashidharan, K. R.; Salarkhan, A. M.; Mahalakshmi, R. (Indian Forester, 2001)
No abstract